2020
DOI: 10.1111/jog.14371
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of co‐existent adenomyosis on outcomes and tumor characteristics of endometrial cancer: A meta‐analysis

Abstract: Objective Published data on the impact of co‐existent adenomyosis on the prognosis of patients with endometrial cancer remains elusive, with studies reporting conflicting results. We conducted this meta‐analysis to evaluate the prognostic significance of co‐existent adenomyosis on clinical outcomes and tumor characteristics of endometrial cancer patients. Methods A comprehensive literature review of multiple databases was conducted; quality assessment of eligible studies was performed by the Newcastle‐Ottawa s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…A recent meta‐analysis found an increased overall survival with a crude HR of 0.51 (95% CI 0.38‐0.69) in 855 women with endometrial cancer and histologically proven adenomyosis, which was similar to our crude HR of 0.63 (95% CI 0.59‐0.69) 7 . They concluded that women with endometrial cancer and adenomyosis had a decreased ratio of deep myometrial invasion, less often had LVSI, more often had low‐grade cancer and early cancer stage.…”
Section: Discussionsupporting
confidence: 89%
“…A recent meta‐analysis found an increased overall survival with a crude HR of 0.51 (95% CI 0.38‐0.69) in 855 women with endometrial cancer and histologically proven adenomyosis, which was similar to our crude HR of 0.63 (95% CI 0.59‐0.69) 7 . They concluded that women with endometrial cancer and adenomyosis had a decreased ratio of deep myometrial invasion, less often had LVSI, more often had low‐grade cancer and early cancer stage.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, An M et al, in their meta-analysis, also indicated that coexistent adenomyosis with endometrial cancer (EC-A) is associated with a favorable prognosis compared to EC. They found a better overall survival rate in EC-A, decreased ratio of Ib according to FIGO (deep myometrial invasion) (OR = 0.45; 95% CI = 0.33–0.60; p < 0.00001) or lymphovascular space invasion [ 57 ]. Worth mentioning is the fact that only parity and not other risk factors for EC differs between patients with EC coexisting with adenomyosis and EC alone [ 58 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Several hypotheses have been proposed to explain the poor prognosis in EC patients with adenomyosis. The large contact area between ectopic endometrium of adenomyosis and the muscular layer might increase the incidence and depth of myometrial infiltration of EC [22,32,33]. Furthermore, EC might follow the spread mechanism of ectopic endometrium through lymph and veins, increasing lymphovascular space invasion [22,34].…”
Section: Accepted Articlementioning
confidence: 99%
“…The large contact area between ectopic endometrium of adenomyosis and the muscular layer might increase the incidence and depth of myometrial infiltration of EC [22,32,33]. Furthermore, EC might follow the spread mechanism of ectopic endometrium through lymph and veins, increasing lymphovascular space invasion [22,34]. In addition, the poor prognosis of EC patients with adenomyosis has been associated with the malignant transformation of adenomyosis [35,36].…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation